Raised interferon‐β, type 3 interferon and interferon‐stimulated genes – evidence of innate immune activation in neutrophilic asthma - da Silva, J.; Hilzendeger, C.; Moermans, C.; Schleich, F.; Henket, M.; Kebadze, T.; Mallia, P.; Edwards, M. R.; Johnston, S. L.; Louis, R. (Clinical and experimental allergy, 2017)
Summary Background Interferons play an important role in innate immunity. Previous studies report deficiency in virus induction of interferon (IFN)‐α, IFN‐β and IFN‐λ in bronchial epithelial and bronchial lavage cells in atopic asthmatics. It is now recognized that asthma is a heterogeneous disease comprising different inflammatory phenotypes, some of which may involve innate immune activation in the absence of overt infection. Objective The aim of this study was to investigate whether the severity of asthma or a specific cellular sputum pattern may be linked to evidence of innate immune activation. Methods Here we investigate the expression of IFN‐β, IFN‐λ1 (IL‐29), IFN‐λ2/3 (IL‐28A/B) and the interferon‐stimulated genes (ISGs) such as myxovirus resistance 1 (Mx1), oligoadenylate synthetase (OAS) and viperin in unstimulated sputum cells in 57 asthmatics (including 16 mild, 19 moderate and 22 severe asthma patients) and compared them with 19 healthy subjects. Results We observed increased expression of IFN‐β, IFN‐λ1/IL‐29, OAS and viperin in asthmatics compared with healthy subjects, while IL‐28 was not expressed in any group. The overexpression was restricted to neutrophilic asthmatics (sputum neutrophils ≥ 76%), while eosinophilic asthmatics (sputum eosinophils ≥ 3%) did not differ from healthy subjects or even showed a lower expression of Mx1. No difference in interferon or ISG expression was observed according to clinical asthma severity. Conclusion and Clinical Relevance Neutrophilic, but not eosinophilic, asthmatics display overexpression of IFN‐β, IFN‐λ1/IL‐29 and ISGs in their sputum cells that may reflect ongoing innate immune activation.